The Implementation of Inquiry Learning Model in Social Science Instruction on Production, Communication, and Transportation Technology to Enhance Learning Motivation and Achievement of 4th Grade Students at Public Elementary School 1 of Mrawan Jember - Rahayu Rahayu; Tituk Handayani (Pancaran Pendidikan, 2017)
This research was conducted in the fourth grade class of Public Elementary School 1 of Mrawan Jember with the purpose of investigating the application of inquiry instructional method to improve the fourth grade student's motivation and learning achievement in Social Science subject concerning Product, Communication, and Transportation Technology. The study was backgrounded by the fact that the students’ learning motivation and learning achievement in the very subject were rather low. The study applied Classroom Action Research (SAC), which was conducted in two cycles carried on for three meetings, through four stages, including planning, implementation, observation, and reflection. The subjects of this research were fourth grade students with the total number of 39 students. Data collection methods applied in this research were observation, interview, documentation, and test. Data Analysis in this research was descriptive qualitative in nature. Based on the results of research, the scores of students’  motivation in the first to the second cycle were 79 (high category) and 88,43% (very high category), subsequent to 9,43% increase, respectively. Based on the analysis on students’ learning achievement, improvement was also evident in that in the first cycle reached they reached 60,1 (medium/enough category) and in the second cycle they gained 81,3 ( very good category).